River deltas: scaling up community-driven approaches to sustainable intensification - CGIAR Research Program on Water, Land and Ecosystems (International Water Management Institute, 2018)
The residents of the Ganges and Mekong River deltas face serious challenges from rising sea levels, saltwater intrusion, pollution from upstream sources, growing populations, and infrastructure that no longer works as planned. In both deltas, scientists working for nearly two decades with communities, local governments and nongovernmental organizations (NGOs) have demonstrated the potential to overcome these challenges and substantially improve people’s livelihoods. There are cost-effective solutions to improving the totality of ecosystem services and market opportunities for young women and men.